Salmonella Weltevreden in integrated and non-integrated tilapia aquaculture systems in Guangdong, China. (August 2017) - Li, Kang; Petersen, Gitte; Barco, Lisa; Hvidtfeldt, Kristian; Liu, Liping; Dalsgaard, Anders
Abstract: Integrated tilapia-pig farming, which uses manure from pigs as fertilizers in fish pond, is a traditional and common production system practised by small-scale farmers in South-east Asia. Although such systems may be environmentally sustainable, they also pose potential food safety hazards including transmission of faecal zoonotic pathogens and accumulation of antimicrobial and other chemical residues. This study aimed to determine differences in occurrence and characteristics of Salmonella spp. isolated from tilapia-pig and non-integrated aquaculture systems in Guangdong province, China. A total of 77 samples (9 pig feed, 19 fish feed, 9 pig faeces, 20 fish mucus and 20 fish intestine) from 10 tilapia-pig ponds and 10 non-integrated ponds were analysed. Salmonella spp. was found in fish mucus (20.0%), fish intestine (40.0%) and pig faeces (11.1%) from integrated ponds, and from fish mucus (40.0%) and fish intestine (40.0%) from non-integrated ponds. S . Weltevreden (76.5%) was by far the most common serovar showing limited antimicrobial resistance. One pig faeces sample contained S . Typhimurium whereas feed samples were found free of S almonella spp.. DNA fingerprinting by the PFGE method showed a clonal relationship of S . Weltevreden which was supported by similar antimicrobial resistance patterns (sulfamethoxazole and trimethoprim resistance) as well as most isolates harbouring a 147-kb sized plasmid. The common finding of S . Weltevreden in both tilapia production systems indicates that this serovar may have a different ecology and increased survival in aquaculture environments in comparison with other Salmonella serovars. Further in vivo studies of the ecology of S . Weltevreden in aquaculture environments are needed. Graphical abstract: Highlights: Clonal Salmonella Weltevreden was isolated from tilapia-pig and non-integrated aquaculture systems in Guangdong province. A similar Salmonella spp. occurrence was found in tilapia-pig and non-integrated aquaculture systems. S . Weltevreden may have different ecology and survival in aquaculture environments compared to other Salmonella serovars.